En analyse af de sønderjyske middelalderkirkers placering i forhold til den samtidige landbebyggelse. - Ethelberg, Per (Arkæologi i Slesvig-Archäologie in Schleswig, 2026)
Already in the mid-1980s, Ebbe Nyborg states that the uncovering of the early interaction between church and settlement in the early Medieval Period ought to be analysed archaeologically (Nyborg 1986, 18). Thirty-five years later, such an analysis is still lacking. It is an extensive task. Perhaps the thoughts presented in this paper can inspire a more in-depth analysis of the large and comprehensive material which Museum Sønderjylland’s excavations of the rural medieval settlements have produced over the past twenty- five years. The point of departure for this analysis is the area overseen by Museum Sønderjylland. The study can be characterised as a random sample analysis with a significance level of approximately 5 %. In analyses based on written sources, one often comes across the term »farm church«. Based on a review of the rural settlement of southern Jutland, it is argued that a »farm church« is hardly a concrete building, but rather a special room which may be furnished with a consecrated altar, presumably in the main house of the farm. One should therefore not expect to find a »farm church« during an archaeological excavation of a rural settlement. It is argued here that the primary consideration for the location of the parish churches has been accessibility for the users of the churches – for the congregation. It has not been a consideration that the church should be built in an existing village. Nor has it been a consideration that the churches should be built on the manor estates.